Electrical stimulation of saccharomyces cerevisiae cultures - Araújo,Ofelia Q.F. (2004)
Modulation of cell endogenous membrane potential by an external electrical field influences the structure and function of membrane compartments, proteins and lipid bi-layer. In this work, the effects of applied potential on Saccharomyces cerevisiae growth were characterized through simple yet conclusive experiments. Cell growth time profile and cell division were investigated as macroscopic response to the electrical stimulation. Control experiments were conducted under identical conditions except for the absence of applied potential. Through comparative analysis, electrical stimulation was verified to alter cell cycle as smaller sized population was observed, suggesting that a synchrony in cell division was promoted. Power spectral analysis was employed to sustain synchrony enhancement, and mathematical modeling was conducted for determining kinetic growth changes. Monod type kinetic parameters for growth were determined by non-linear regression. The affinity constant (namely kS) presented a dependence on applied potential suggesting changes on transport across cell membrane. Electrochemically promoted stress was also verified to inhibit growth as well as to induce changes on cell viability.